Central banks in the age of the euro : Europeanization, convergence, and power - Dyson, Kenneth H. F.; Marcussen, Martin (Oxford University Press, 2009)
Both studies of political power and Europeanization studies have tended to neglect central banks. As the age of the euro reaches its 10th anniversary, it is timely to reflect on what it means for central banks, which have been at the forefront of the establishment of Economic and Monetary Union in the European Union. Central banks have been caught up in a major historic political project. What does it mean for them? What does the age of the euro tell us about the power of centralbanks, their Europeanization and whether they are coming to resemble each other more closely? This book brings toget.